Stabilization of a class of underactuated vehicles with uncertain position measurements and application to visual servoing. (March 2017) - de Plinval, Henry; Morin, Pascal; Mouyon, Philippe
Abstract: Stabilization of a class of underactuated vehicles with uncertain measurements of the position tracking error is addressed. Nonlinear feedback laws ensuring semi-global stability for a large class of uncertainties on these measurements are derived based on properties of saturated controls. Practical relevance of the proposed results is illustrated by two application examples for Vertical Take-Off and Landing aerial vehicles equipped with a mono-camera sensor: point stabilization in front of a planar target and visual way-points navigation based on interpolation of homography measures.